Topography dependence of conductivity in electrostrictive germanium sulfide nanoribbons. (1st October 2022) - Chen, Zhangfu; Hoang, Anh Tuan; Seo, Dongjea; Cho, Minhyun; Kim, Young Duck; Yang, Lianqiao; Ahn, Jong-Hyun; Choi, Heon-Jin
Abstract: Layered group IV monochalcogenides have garnered considerable attention as a new class of two-dimensional (2D) semiconducting materials owing to their unique crystal structure and novel physical properties. The present work describes the chemical vapor transport synthesis of single-crystalline GeS nanoribbons. The findings demonstrate that with incrementally applied voltage, electrostrictive deformation and highly vertical current occur more significantly. Additionally, using a 2D fast Fourier transform power spectra, we demonstrate that the horizontal distribution of topography and current is more inhomogeneous than the vertical distribution, and that their monolithic spatial correlation weakens with increasing applied voltage. Moreover, we discovered that electrostrictive deformation has a sizable effect on the monolithic vertical resistance. Furthermore, local hollow positions are more conductive than bulge positions, as demonstrated by the 'resistor' model and local current–voltage curve. These findings on layered GeS nanoribbons not only shed light on the topographic and electrical properties of the material but also expand the possibilities for other nanoscale electronic and electromechanical device applications.